2018
DOI: 10.1509/jm.15.0511
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Optimal Donation Solicitation: Evidence from the Field of the Differential Influence of Donor-Related and Organization-Related Information on Donation Choice and Amount

Abstract: The present research decomposes consumer donation behavior into two components: donation choice (i.e., whether to donate) and donation amount (i.e., how much to donate). It then considers how information related to the donor and information related to characteristics of the soliciting organization may differentially influence the two decisions. Results from four field experiments suggest that donor-related appeals have a greater effect on the donation choice decision (vs. organization-related appeals), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 31 publications
5
54
0
1
Order By: Relevance
“…Second, through additional analysis, this study settles the problem of using consequent variables raised by a recent study on donation behavior [56]. The research model of this study has even more significant meaning as a donation behavior decision model of online donors as it confirmed that the results of the study when donation intention is used as the consequent variable are not different from those when the donation amount is used as the consequent variable.…”
Section: Summary Of Findings and Implicationssupporting
confidence: 62%
See 1 more Smart Citation
“…Second, through additional analysis, this study settles the problem of using consequent variables raised by a recent study on donation behavior [56]. The research model of this study has even more significant meaning as a donation behavior decision model of online donors as it confirmed that the results of the study when donation intention is used as the consequent variable are not different from those when the donation amount is used as the consequent variable.…”
Section: Summary Of Findings and Implicationssupporting
confidence: 62%
“…Most prior studies of individuals' donation behavior have selected either choice (whether to make donation or not) or amount (level of donation amount) as the result of donation marketing and assumed that the result would be the same if they had chosen the other variable [54,55]. However, researchers have recently understood the outcome of donation marketing in a multi-dimensional manner and point out the problem that these two consequent variables (donation intention and amount of donation) may have different causal relationships with various antecedents [56]. Therefore, in the additional analysis of this study, we examine the problem raised by the prior studies by analyzing the study model through the application of donation amount as a consequent variable.…”
Section: Stimuli and Measuresmentioning
confidence: 99%
“…Future work can also investigate how certain types of feeling states might interact with the framing of the donation decision. Deciding to donate money is different from deciding how much to allocate to a given cause (Dickert, Sagara, and Slovic 2011;Fajardo, Townsend, and Bolander 2018). While research may show positive effects for one type of prosocial measure, there may be negative effects for the other.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
“…13 While self-efficacy reflects one's beliefs about his/her ability to perform a behavior. 14 Apart from this, organizational credibility, as a global evaluation of an organization's capability to uphold its promises, has been shown to influence donation amounts but not donation choice, 15 and organizational credibility is less actionable for it can take significant time to meaningfully establish or change. 16 Moves management is a term used primarily with the non-profit sector in relationship to donor development, and it is developed by David R. Dunlop, the Cornell University fundraiser, defined it as, "changing people' s attitudes so they want to give."…”
Section: Literature Reviewmentioning
confidence: 99%